EFFECT OF SOLVENT EXTRACTED KARANJ CAKE WITH ENZYMES AND LIVER TONIC SUPPLEMENTATION ON PERFORMANCE, NUTRIENT DIGESTIBILITY AND ECONOMICS OF BROILER CHICKEN - M.V.L.N. RAJU; SRINIVAS GURRAM, DAIDA KRISHNA, V. RAVINDER REDDY, V. CHINNI PREETHAM (The Journal of Research, PJTSAU, 2022)
An experiment was conducted to evaluate the effect of dietary inclusion of solvent extracted karanj cake (SKC) and iso propyl alcohol (IPA) treated SKC supplemented with protease (4000 U/kg), phytase (400 U/kg) and liver tonic (0.1%) on performance, nutrient digestibility and returns over feed cost in broiler chickens. The inclusion of control and karanj cake were included in diets on isocaloric and isonitrogenous basis at graded (6%) level making 12 treatments (T1 to T12). A total of 360 dayold commercial broiler chicks, which were distributed in a randomized block design into 12 groups with 6 replicates of 5 chicks each. The chicks were housed in battery brooders and fed experimental diets from 1 to 42 days of age. The results revealed that inclusion of IPA treated karanj cake and SKC at 6% level treated with enzymes and liver tonic supplementation significantly did not improve the body weight gain, feed intake and feed conversion ratio compared to control groups. The percent retention of dry matter and crude protein were significantly (P<0.05) higher in control group compared with 6% SKC and IPA treated karanj cake with enzymes or liver tonic supplementation at 6th week of age. Mortality on karanj cake diets was within the limits. The 6% IPA treated karanj cake & SKC of the dietary treatments with or without supplementation of enzymes and liver tonic recorded returns over feed cost was lower compared to control. It can be concluded that, supplementation of enzymes / liver tonic could not alleviate the toxic effects of solvent extracted karanj cake or IPA treated karanj cake at 6% level in the diet.